Implementation of a Precision Oncology Program as an Exemplar of a Learning Health Care System in the VA - Fiore, Louis (Fed Pract, 2016)
The program determines and disseminates precision oncology best practices; enhances patient and provider engagement; and fosters collaboration among the VA, National Cancer Institute, academia, other health care systems, and industry to provide cancer patients with access to clinical trial participation.